Pro-necrotic molecules impact local immunosurveillance in human breast cancer - Gautier Stoll; Yuting Ma; Heng Yang; Oliver Kepp; Laurence Zitvogel; Guido Kroemer (OncoImmunology, 2017)
Necrosis culminates in spilling cellular content through the permeabilized plasma membrane, thereby releasing potentially immunostimulatory molecules in the pericellular space of dead cells. Accordingly, molecules involved in necroptotic signaling, such as receptor-interacting serine/threonine-protein kinase 3 (RIPK3) and mixed lineage kinase-like (MLKL) have been found to stimulate anticancer immune responses in mouse models of chemotherapy. mRNAs encoding prominent pro-necrotic gene products (RIPK1, RIPK3, MLKL, PGAM5 and DFNA5) were correlated with immune-related metagenes in several cancer types (breast, colorectal, lung, ovary, melanoma), revealing the strongest associations in breast cancer. In two independent breast cancer cohorts, the expression of MLKL and DFNA5 was decreased at the mRNA levels in tumor as compared with normal tissues. Moreover, MLKL expression exhibited a strong positive correlation with genes reflecting the presence of B, NK and T lymphocytes in the tumor bed, in multiple distinct breast cancer subtypes. In contrast, the positive correlation between RIPK3 and lymphoid cells was restricted to HER2+ and triple negative/basal-like breast cancer. Moreover, the expression of DFNA5, which mediates post-apoptotic secondary necrosis, mostly correlated with the monocytic lineage and macrophages in ER+/luminal A breast cancers. MLKL (and to some extent RIPK1 and RIPK3) was strongly associated with the local expression of genes involved in interferon-α and interferon-γ responses. Altogether, these results support the idea that pro-necrotic signaling facilitates intratumoral immune responses in human breast cancer.